Development and Validation of a Scale for Measuring Sustainability Factors of Informal Microenterprises: A Qualitative and Quantitative Approach - Khan, E.; Quaddus, Mohammed (-, 2015)
The growing interest in sustainability has dominated the area of entrepreneurship research. However, the measuring of sustainability factors has been largely ignored. As a result, so far, no researchers have developed sustainability factor scales and this might lead to a question of scale validity. This paper attempts to fill this gap: the aim of this study is to develop and validate scales of sustainability factor by investigating a microenterprise from the informal sector. In its design, the study uses a mixed method research approach. In the qualitative phase, content analysis has been applied to analyse the transcribed field study interviews. This procedure explores and confirms the sustainability variables and factors. The quantitative data are analysed through Exploratory Factor Analysis (EFA) followed by Partial Least Square (PLS) approach. Quantitative analysis then validates the variables and factors. The study then specifies scales of sustainability factors in the context of an informal microenterprise and assesses them as reflective in nature. The limitations of the study are then identified and thoughts to stimulate future investigations discussed.